Surgical risk of preoperative malperfusion in acute type A aortic dissection - Girdauskas, Evaldas; Kuntze, Thomas; Borger, Michael A.; Falk, Volkmar; Mohr, Friedrich-Wilhelm (The Journal of thoracic and cardiovascular surgery, 2009)
Patients who have type A dissection with preoperative malperfusion syndromes are believed to be at extremely high surgical risk. Our aim was to evaluate perioperative and long-term results of patients with preoperative malperfusion. A total of 276 patients (174 men; mean age 59.5 ± 13.4 years) underwent surgery for acute type A dissection between October 1994 and January 2008. Preoperative malperfusion syndromes were diagnosed in 93 (33.7%) patients (group I) and involved coronary circulation in 41 (15%) patients, central nervous system in 39 (14%) patients, limb ischemia in 32 (11.6%) patients, and mesenteric circulation in 8 (3%) patients. Postoperative results were compared between patients with preoperative malperfusion and those without this complication (group II, n = 183). In-hospital mortality was 29.0% in group I versus 13.6% in group II ( P = .002). The postoperative intensive care unit stay was longer (11.4 ± 9.7 vs 7.7 ± 6.9 days; P = .04) in the malperfusion group. A total of 6 (75%) patients with mesenteric malperfusion died. Long-term follow-up (range, 1–122 months postoperatively) was available in 100% of survivors. One-year and 5-year overall survivals were 49.8% ± 11.8% and 41.8% ± 12.6% in group I versus 70.4% ± 7.6% and 56% ± 10.4% in group II ( P = .005). Cox regression analysis identified preoperative malperfusion as a significant risk factor for long-term mortality after surgery for type A dissection (hazard ratio, 1.7; 95% confidence intervals, 1.2–3.1). Preoperative malperfusion is a significant risk factor influencing perioperative and long-term survival after surgery for acute type A dissection. Percutaneous interventional procedures and delayed surgery should be considered in patients with clinically apparent mesenteric malperfusion because of the dismal prognosis of immediate surgical therapy.